THE EFFECT OF HIGH FLUORIDE INTAKE ON SODIUM, AND POTASSIUM AND CALCIUM LEVELS IN SHEEP BLOOD SERUM - S.M., Hussain; N.M‎., Al-Shathir,; Kh.K‎, Kudhaier,; A.W.R. ‎, Mehdi, (The Iraqi Journal of Veterinary Medicine, 1987)
This experiment was carried out to investigate levels of sodium, potassium and calcium in ovine blood serum for 12 weeks during which fluoride (100 ppm) was added to the ration. The rams remained physically in good condition and there were no lesions in the teeth, gums and joints. With the exception of an increase in sodium at the end of the first week, sodium and potassium levels were not influenced. This finding could point out to the possibility of failure of the added fluoride to induce significant changes in kidney and aldosterone functions regarding regulation of these two ions in blood. There was a general tendency of the total calcium level to decrease which reached statistical significance in samples of three weeks. Such decrease could be due to a decline in calcium intestinal absorption and an increase in bone deposition and excretion with urine.